Strategies to control the growth of unwanted microalgae during the production of Arthrospira platensis BEA 005B - Silvia Villaró; Sandra Valero-Cardoso; Cristina Cerdá-Moreno; Martina Ciardi; Tomás Lafarga (Cleaner Engineering and Technology, 2025)
When producing Arthrospira platensis (Spirulina) it is essential to reuse the exhausted culture medium for sustainability reasons. However, this strategy is challenging given the negative effect the medium has on microalgal growth. While recycling helps reduce costs and environmental impact, it can also result in an increased risk of biological contamination. Indeed, in this study, harvesting Arthrospira platensis using a 100 μm mesh led to an accumulation of an unwanted microalga identified as Chlorella sp. To address this issue, various strategies were evaluated. These included the use of sea salt, increasing the pH, heating the culture, or adding an additional ultrafiltration step. The results showed that the most effective solution was to incorporate a 0.2 μm membrane filter. This technique eliminated the Chlorella sp. cells from the culture medium, resulting in a 15 % increase in the A. platensis biomass production compared to unfiltered cultures. Adjusting the pH of the culture to 10.5 also limited the growth of Chlorella sp. without significantly affecting A. platensis growth. This strategy proved suitable for delaying the accumulation of Chlorella sp. but did not avoid its appearance. The findings reported in this work underscore the importance of choosing appropriate separation methods to ensure the purity and productivity of A. platensis cultures in large-scale production systems.